A comparison of zinc interactions with succinylated milk protein concentrate and sodium caseinate. (1st March 2022) - Shilpashree, B.G.; Arora, Sumit; Chawla, Prince; Sharma, Vivek
Abstract: Milk proteins with substantial reactive groups enable new protein chemistries and succinylation being a potential post-translational modification plays a significant role in regulating milk protein configuration properties. The presence of additional carboxylic group due to succinylation also improves the divalent metal binding efficiency of milk proteins. Therefore, in the present research work, the interaction of zinc (Zn) with native and succinylated milk protein concentrate (MPC) and sodium caseinate (NaCN) was assessed. For the optimization of milk protein-Zn complexes, a diafiltration process was adopted and this process efficiently removed the free form of succinic acid which was confirmed by scanning electron microscopy. Maximum Zn binding ability of MPC and succinylated MPC (SMPC) was observed at 2.0 and 7.0 mmol/L Zn concentration, whereas NaCN and SNaCN showed maximum Zn binding ability at 2.4 and 7.6 mmol/L Zn concentrations, respectively. Processing variables such as pH and thermal treatment did not alter the Zn holding capacity of SMPC and SNaCN, however, ionic concentration ≥0.3 mol/L NaCl significantly decreased (P < 0.05) it. Therefore, based on the key findings, the milk protein-Zn complex can be utilized for the fortification of various food products to eradicate Zn deficiency. Highlights: Zn binding ability of MPC and NaCN increased drastically upon succinylation. Diafiltration adopted in the method reduced excess SA from protein-zinc complexes. SMPC showed better zinc holding capacity than SNaCN under various conditions. SNaCN-zinc complex showed better zinc retention, solubility and yield.